Condom use and prevalence of syphilis and HIV among female sex workers in Andhra Pradesh, India – following a large-scale HIV prevention intervention - Rachakulla, Hari Kumar (BioMed Central, 2011)
BACKGROUND: Avahan, the India AIDS initiative began HIV prevention interventions in 2003 in Andhra Pradesh (AP) among high-risk groups including female sex workers (FSWs), to help contain the HIV epidemic. This manuscript describes an assessment of this intervention using the published Avahan evaluation framework and assesses the coverage, outcomes and changes in STI and HIV prevalence among FSWs. METHODOLOGY: Multiple data sources were utilized including Avahan routine program monitoring data, two rounds of cross-sectional survey data (in 2006 and 2009) and STI clinical quality monitoring assessments. Bi-variate and multivariate analyses, Wald Chi-square tests and multivariate logistic regressions were used to measure changes in behavioural and biological outcomes over time and their association. RESULTS: Avahan scaled up in conjunction with the Government program to operate in all districts in AP by March 2009. By March 2009, 80% of the FSWs were being contacted monthly and 21% were coming to STI services monthly. Survey data confirmed an increase in peer educator contacts with the mean number increasing from 2.9 in 2006 to 5.3 in 2009. By 2008 free and Avahan-supported socially marketed condoms were adequate to cover the estimated number of commercial sex acts, at 45 condoms/FSW/month. Consistent condom use was reported to increase with regular (63.6% to 83.4%; AOR=2.98; p<0.001) and occasional clients (70.8% to 83.7%; AOR=2.20; p<0.001). The prevalence of lifetime syphilis decreased (10.8% to 6.1%; AOR=0.39; p<0.001) and HIV prevalence decreased in all districts combined (17.7% to 13.2%; AOR 0.68; p<0.01). Prevalence of HIV among younger FSWs (aged 18 to 20 years) decreased (17.7% to 8.2%, p=0.008). A significant increase in condom use at last sex with occasional and regular clients and consistent condom use with occasional clients was observed among FSWs exposed to the Avahan program. There was no association between exposure and HIV or STIs, although numbers were small. CONCLUSIONS: The absence of control groups is a limitation of this study and does not allow attribution of changes in outcomes and declines in HIV and STI to the Avahan program. However, the large scale implementation, high coverage, intermediate outcomes and association of these outcomes to the Avahan program provide plausible evidence that the declines were likely associated with Avahan. Declining HIV prevalence among the general population in Andhra Pradesh points towards a combined impact of Avahan and government interventions.